Democratic Republic of Sao Tome And Principe : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of Sao Tome And Principe. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Sao Tome and Principe's Request for Disbursement Under the Rapid Credit Facility (RCF). The authorities of Sao Tome and Principe have moved swiftly to develop a plan to address the major challenges posed by the coronavirus disease 2019 pandemic. The authorities plan to increase well-targeted health and social spending to assist the most vulnerable, support the unemployed, incentivize private businesses to retain workers, and enhance fiscal transparency and good governance. These steps would help cushion the economic impact while ensuring that public funds are spent appropriately. Prudent loan restructuring while maintaining prudential standards will help alleviate liquidity pressures and safeguard financial stability. The authorities' policies focus on immediate measures to protect against the virus, assistance to the most vulnerable, and countercyclical measures during this crisis. Public financial management will be reinforced to ensure the disbursement is used appropriately and steps will be taken to speed up the recovery next year. The IMF staff assesses that the eligibility requirements for the RCF are met and supports the authorities' request. While the country is in debt distress due to long-standing external arrears, the debt level is deemed sustainable, and there is adequate capacity to repay the IMF. The financing would help prevent a much more severe and prolonged contraction, with a substantial social impact.